Compressive resistance of high-strength and normal-strength steel CHS members at elevated temperatures. (July 2020) - Kucukler, Merih
Abstract: The compressive behaviour of hot-finished circular hollow section (CHS) steel members in fire is investigated in this paper through numerical modelling. CHS members with high-strength steel grades of S690 and S460 are taken into consideration in addition to those made up of normal-strength grades S355, S275 and S235. Numerical models of CHS structural steel members able to replicate their response in fire are validated. Using the validated finite element models, extensive parametric studies are carried out for the purpose of exploring a broad range of factors influencing the cross-section and member buckling response of CHS steel members under axial compression at elevated temperatures. The accuracy and safety of the design recommendations provided in the European structural steel fire design standard EN 1993-1-2 for the determination of the axial compression resistances of CHS steel members in fire are assessed. New design methods able to provide accurate and safe estimations of the cross-section axial compression resistances and flexural buckling resistances of CHS steel members at elevated temperatures are proposed. The higher accuracy, reliability and safety of the proposed design methods relative to the existing design provisions in EN 1993-1-2 are illustrated. Highlights: Behaviour and design of high-strength and normal-strength steel CHS members under compression in fire are investigated. FE models able to mimic response of CHS steel columns in fire are developed and validated using results from experiments. New design rules for cross-section and flexural buckling resistance of CHS steel columns in fire are established. Proposed design rules lead to more accurate results relative to the current design rules in EN 1993-1-2. Accuracy, safety and reliability of proposed design rules are verified against extensive numerical data.